Genetic characterization of a novel recombinant echovirus 30 strain causing a regional epidemic of aseptic meningitis in Hokkaido, Japan, 2017 - Miyoshi, Masahiro; Goto, Akiko; Komagome, Rika; Yamaguchi, Hiroki; Maruo, Yuji; Nakanishi, Masanori; Ishida, Setsuko; Nagano, Hideki; Sugisawa, Takahisa; Okano, Motohiko (Archives of Virology, 2020)
A regional epidemic of aseptic meningitis caused by echovirus 30 (E30) occurred in Hokkaido, Japan, during the period of August-December 2017. To investigate their phylogenetic relationship to other human enteroviruses, we determined the complete genomic nucleotide sequences of isolates from this outbreak. Phylogenetic analysis of the viral capsid protein 1 gene showed that the strains were most closely related to E30 strains detected in Germany, France, and Russia in 2013. In contrast, the region encoding the viral protease and the RNA-dependent RNA polymerase had a close phylogenetic relationship to non-E30 enteroviruses detected in the United Kingdom and Switzerland in 2015-2017, suggesting that a recombination event had occurred.